Generation of three-cycle multi-millijoule laser pulses at 318 W average power - Nagy, Tamas; Haedrich, Steffen; Simon, Peter; Blumenstein, Andreas; Walther, Nico; Klas, Robert; Buldt, Joachim; Stark, Henning; Breitkopf, Sven; Jojart, Peter; Seres, Imre; Varallyay, Zoltan; et al. (Optica, 2019)
The generation of three-cycle multi-millijoule pulses at 318 W power is reported by compressing pulses of a Yb-fiber chirped pulse amplifier in a 6 m long stretched flexible hollow fiber. This technique brings high-power lasers to the few-cycle regime.
CRIS-Team Scopus Importer:2023-04-20